Performance of multiwavelength laser utilizing Fabry-Pérot interferometer in different cavity configuration using hybrid raman-EDF gains / Nani Fadzlina Naim ...[et al.] - Naim, Nani Fadzlina; Ibrahim, Muhammad Faiz; Sarnin, Suzi Seroja; Ya’acob, Norsuzila (UiTM Press, 2022)
This paper presents on the design of multiwavelength laser for hybrid Raman-erbium doped fiber gains in three different cavities; single pass linear, bidirectional linear and ring laser. Multiwavelength laser has the potential for its simplicity and lower in cost. The 50% arm coupling ratio of ring laser structure with 0.2 nm line width, 20 lasing line and 5 mW lasing threshold is achieved and shown to be the best result for multiwavelength laser design compared to the single pass and bidirectional linear cavity. With an input power of 240 mW (EDFA) and 2000 mW (FRA), a 96% power conversion efficiency is obtained and produced a stable multiwavelength for L-band source with peak power of -10 dBm for ring laser, -25 dBm for single pass linear and -5 dBm for bidirectional linear laser. The lasing threshold obtained at 50% arm coupling ratio for ring laser is also slightly lower than other value reported previously. The interesting features of the proposed laser systems is the low threshold power, high output power, high number of lasing line and high pump conversion efficiency.